The case of the blazing sky - Erickson, John R.; Holmes, Gerald L. (New York : Viking, 2008)
With the threat of prairie fires looming, security expert Hank the Cowdog takes on extra duties as Head of Fire Safety, while trying to resist the mouth-watering hens in Sally May's chicken house.
Keywords: Dogs; Ranch life -- Texas; Fires; Humorous stories; Hank the Cowdog (Fictitious character); Ranch life -- Texas; High interest-low vocabulary books